2017
DOI: 10.1159/000480013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fetomaternal Outcome between 47 Deliveries Following Successful External Cephalic Version for Breech Presentation and 7456 Deliveries Following Spontaneous Cephalic Presentation

Abstract: Background: Achieving a cephalic position after a successful external cephalic version (ECV) is desired to result in delivery and fetal outcomes that are similar to those of deliveries following spontaneous cephalic presentation. Methods: We performed a retrospective cohort study including patients with successful ECV following fetal breech position (ECV cohort, n = 47) or with a singleton spontaneous cephalic pregnancy at ≥37 weeks of gestational age (control group, n = 7,456) attempting a vaginal delivery be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…A metaanalysis published in 2004 concluded that intrapartum CS rate after successful ECV was two times of that spontaneous cephalic pregnancies [45]. Isakov et al compared the delivery condition of 47 patients accepting successful ECV and 7456 patients with spontaneous cephalic presentation, which also found that the prior had higher cesarean delivery rate (27.7% vs 12.8%) [46]. It should be noteworthy that pregnancies after successful version should not be considered the same as a normal pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…A metaanalysis published in 2004 concluded that intrapartum CS rate after successful ECV was two times of that spontaneous cephalic pregnancies [45]. Isakov et al compared the delivery condition of 47 patients accepting successful ECV and 7456 patients with spontaneous cephalic presentation, which also found that the prior had higher cesarean delivery rate (27.7% vs 12.8%) [46]. It should be noteworthy that pregnancies after successful version should not be considered the same as a normal pregnancy.…”
Section: Discussionmentioning
confidence: 99%